Remote hearings in the social security tribunal: should we be worried? - Burton, M (Sweet and Maxwell, 2021)
Considers the implications of the introduction of remote hearings in the First-tier Tribunal Social Entitlement Chamber during the coronavirus pandemic. Reviews the procedural background to such hearings, and evaluates their impact in relation to verbal and non-verbal communication, emotional engagement and vulnerable appellants. Discusses the dangers posed for unrepresented parties in fact-finding hearings, and their access to justice.